Pengangkut Muatan Kapasitas 2 kg Berbasis Mikrokontroler - Syahwir, Irawati Dewi; Nainggolan , Thomas Rocky Roganda (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2024)
Energy transformation is growing, and trade is becoming more complex and dynamic regarding energy efficiency and flexible production design. The development of a semi-automatic transporter aims to improve intralogistics' flexibility whereas the electrical power requirements and time efficiency can be analyzed. The analysis method measures the rotational speed of the semi-automatic transport wheel and identifies its model. The rotation speed of the wheels on a semi-automatic transporter is based on translational movement, rotary movement, and transport and load. The measurement results show that the energy requirements for translational and rotational movements increase due to the mass of the charge. However, in the same situation, an increase in the speed value of the semi-automatic transporter results in lower energy requirements, even though the need for electrical power is increasing. The capacity of the DC motor decreases with increasing load, namely from 239.184 rpm to 166.204 rpm, and likewise for the battery from 20000 mhA to 5400 mhA. In dynamic measurement conditions, namely, measurements made while the motorbike is running, there is an average measurement error of –0.11 cm to –0,03 cm in backward movements.